Hybrid hydrophilic polymer/montmorillonite systems - Drzycimska, A.; Spychaj, T. (Polimery, 2022)
A literature review on hybrid systems consisted of hydrophilic polymer (cationic, anionic or nonionic one) and montmorillonite (MMT, Fig. 1 and 2) is presented. The methods of preparation, evaluation and applications directions are discussed. Preparation of such products let modify the functional properties of polymers. The hybrid systems based on polyacrylamide (PAAm) (Fig. 3-5), acrylamide copolymers, polyvinylpyrrolidone (PVP), poly(acrylic acid) (PAA) (Fig. 6), poly(ethylene oxide) (PEO), oligomers or polymers of ethylene glycol (Fig. 7) or polymer of natural origin - starch, containing montmorillonite were characterized in detail.